1993
DOI: 10.3168/jds.s0022-0302(93)77628-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Contamination of Raw Milk by Listeria monocytogenes in Dairy Farms

Abstract: A case-control study involving 128 selected dairy farms was conducted to assess the association of several suspected risk factors with the odds of contamination of raw milk by Listeria monocytogenes. Using logistic regression, we found that poor quality of silage (pH > 4.0), inadequate frequency of cleaning the exercise area, poor cow cleanliness, insufficient lighting of milking barns and parlors, and incorrect disinfection of towels between milkings were significantly associated with milk contamination by L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 18 publications
2
98
1
8
Order By: Relevance
“…Feeding dairy cattle with improperly fermented silage was found to be significantly associated with contamination of bulk milk with L. monocytogenes (Sanaa et al, 1993). Listeria spp.…”
Section: Contamination Within Silage Balesmentioning
confidence: 99%
See 2 more Smart Citations
“…Feeding dairy cattle with improperly fermented silage was found to be significantly associated with contamination of bulk milk with L. monocytogenes (Sanaa et al, 1993). Listeria spp.…”
Section: Contamination Within Silage Balesmentioning
confidence: 99%
“…Antognoli et al (2009) reported that geographical location and herd size affected rates of L. monocytogenes contamination in bulk milk, with the risk of contamination increasing according the herd size. Cleanliness in the animal exercise area was also related to low levels of bulk milk contamination (Sanaa et al, 1993).…”
Section: Raw Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of listeriosis in sheep and goats has been associated with the feeding of silage contaminated with L. monocytogenes (43,45). Furthermore, there is evidence that poor-quality silage is one of the primary sources of contamination of raw milk by L. monocytogenes (33). The growth and survival of listeria in silage are dependent on the degree of anaerobiosis and on the pH.…”
Section: Listeriamentioning
confidence: 99%
“…coli O157: H7 and Salmonella spp have also been the cause of udder infection in cows (Kousta et al, 2010;Sanaa, Poutrel, Menard, & Serieys, 1993). Incidence of pathogens in milk is also influenced by farm size, number of animals on the farm, hygiene, farm management practices, geographical location, and season (Oliver, Jayarao, & Almeida, 2005).…”
Section: Sources Of Cheese Contaminationmentioning
confidence: 99%